Evaluation of Relative Yeast Cell Surface Hydrophobicity Measured by Flow Cytometry. Issue 1 (2005) - Colling, Lisa; Carter, Richard N.; Essmann, Michael; Larsen, Bryan
Abstract : Objective: To develop an efficient method for evaluating cell surface hydrophobicity and to apply the method to demonstrate the effects of fungal growth conditions on cell surface properties. Methods: Yeast isolates were suspended in phosphate-buffered saline and mixed with deep blue-dyed polystyrene microspheres. Flow cytometry was used to detect the degree of microsphere binding to yeast cells. Different strains of yeast were compared for intrinsic microsphere binding activity and changes in growth conditions were invoked to modify the relative surface hydrophobicity. Results: Commercially available blue-dyed polystyrene microspheres showed strong fluorescence in the FL3 channel, whereas yeast cells did not show appreciable FL3 fluorescence. Microspheres and yeast were generally distinguishable on the basis of size revealed by forward light scatter. This method showed a wide variation in intrinsic cell surface hydrophobicity among Candida albicans strains. Likewise, variation in hydrophobicity of non-albicans yeast species was observed. Growth on solid media, incubation at 25°C, or 250 mg/dl glucose concentration increased hydrophobicity compared with growth in liquid media, incubation at 37°C, or 50 mg/dl glucose, respectively. Growth in1 × 10 − 9 M estradiol had no appreciable effect on hydrophobicity. Conclusions: Stained latex microspheres fluoresced in the FL3 channel of the flow cytometer and bound to yeast cells to an extent related to the surface hydrophobicity of the yeast. Binding detected by flow cytometry showed that clinical yeast isolates varied in intrinsic binding capacity and this binding ability was altered by different growth conditions. The implications for virulence regulation among yeast isolates are discussed.